Prognosis after radical esophagectomy for adenocarcinoma of the esophagus according to Laurén classification and c-erbB-2 oncogene overexpression - J.W. ten Kate, Fiebo; Johan A. Offerhaus, G.; Obertop, Hugo; Jan B. van Lanschot, J.; W. van Sandick, Johanna; Polkowski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2000)
The aim of this study was to investigate the prognostic significance of the Laurén classification and c- erbB -2 oncogene overexpression in adenocarcinoma of the esophagus and/or gastro-esophageal junction (GEJ). Forty-one adenocarcinomas of the esophagus and/or GEJ were reviewed for tumor stage, Laurén classification, and c- erbB -2 by immunohistochemistry. According to the Laurén classification, tumors were classified as intestinal, mixed, or diffuse in 54%, 32%, and 15%, respectively. Diffuse tumors had a significantly worse prognosis than intestinal tumors. The prognostic value of the Laurén classification was independent of stage. C- erbB -2 overexpression was detected in 24% of the tumors and was present exclusively in intestinal tumors and in intestinal-type areas of mixed tumors. Ten of the 30 stage III/IV tumors were c- erbB -2 positive, while none of the 11 stage I/II tumors overexpressed the oncogene product. Conclusions: 1) the Laurén classification is independent prognostic factor in adenocarcinoma of the esophagus and GEJ, 2) intestinal and diffuse tumors differ oncogenetically, 3) c- erbB -2 overexpression is associated with stage of disease.